Section 375 Exception, Explanations and Section 375A Malaysian Penal Code –Legitimising Rape within Marriage: A Call for Reform - Balasingam, Usharani; Sabaruddin, Johan Shamsuddin (Journal of Malaysian and Comparative Law, 2015)
This paper’s objective is to consider the constitutionality and defensibility of exception and explanations under s375 of the Malaysian Penal Code (Penal Code) which legitimises the offence of rape committed by a husband on his wife. Section 375A will also be considered to see if it provides a cure for the contravention. The current law legitimises rape committed within marriage. The rationale for the differentiation in treatment of rape within and outside marriage is explored and discussed. The justification for maintaining the provision in the current day setting considering the development of society, particularly with respect to women, who have gone from being treated as chattels or possessions to legal persona having rights and entitlements including the right to vote and rights under local laws, and international and regional conventions, is discussed. The relevance of the provision today and the need for reform of the Penal Code provisions to ensure compliance with the Malaysian Federal Constitution (Federal Constitution) in spirit and form and with current policies, regional and international conventions and the Islamic perspective are discussed. The relevance of local legislation such as the Malaysian Domestic Violence Act 1994 (Domestic Violence Act) and the effectiveness of the same in achieving the outcome of the policy and objective of the Act from the perspective of a rape offence are also discussed. The movement for reform to update outdated concepts currently reflected in present laws and to embody the current spirit and form of women’s status and rights as humans within society is a call much repeated and yet still ignored. This paper strives to keep alive the call for reform reminding all concerned of the jarring discrepancies between the Penal Code and the Federal Constitution and Malaysian State responsibility under regional, international human rights instruments and Islamic principles. The recommendation is to delete the s375 Penal Code exception, explanations and s375A.